2017
DOI: 10.1177/0218492317744902
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial effusion following cardiac surgery. A single-center experience

Abstract: Background Pericardial effusion is still a common postoperative complication after open heart surgery with cardiopulmonary bypass. Pericardial effusion significantly prolongs the hospital stay and associated costs as well as affecting overall outcomes after open heart surgery in Hanoi Heart Hospital, a tertiary hospital in Vietnam with an annual volume of 1000 patients. This study aimed to investigate the clinical presentation, incidence, and risk factors of postoperative pericardial effusion, which may ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 12 publications
(30 reference statements)
1
20
1
1
Order By: Relevance
“…Patients that were younger, male, had increased alcohol consumption and underwent mitral valve surgery compared with aortic valve surgery had an increased risk of readmission due to effusions. Previous studies have suggested arrhythmias, larger body surface area, anti‐coagulation treatment, and cardiac enlargement are associated with pericardial effusion 18–20 . Earlier studies have focused on factors associated with the development of effusions in general, including in the early postoperative period during the index admission, rather than factors associated with readmissions 18,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients that were younger, male, had increased alcohol consumption and underwent mitral valve surgery compared with aortic valve surgery had an increased risk of readmission due to effusions. Previous studies have suggested arrhythmias, larger body surface area, anti‐coagulation treatment, and cardiac enlargement are associated with pericardial effusion 18–20 . Earlier studies have focused on factors associated with the development of effusions in general, including in the early postoperative period during the index admission, rather than factors associated with readmissions 18,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Permanent pacemaker, n (%) 6 (2) [18][19][20] Earlier studies have focused on factors associated with the development of effusions in general, including in the early postoperative period during the index admission, rather than factors associated with readmissions. 18,20 Furthermore, predicting readmissions due to pericardial effusions might also be difficult, as the risk of atrial fibrillation increases as a Mechanical aortic valve 52 (21) 100 (14) .010* 15 (13) 85 (14) .768…”
Section: Preoperative Informationmentioning
confidence: 99%
“…Echocardiography is a well-utilized diagnostic tool in the assessment of pericardial effusion (9). Nevertheless, postoperative echocardiography is not always performed before hospital discharge after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusion is a known complication of open cardiac surgery with 1-3% of patients needing intervention [1][2][3]. Postoperative pericardial effusion secondary to bleeding into the pericardial sac is commonly identified prior to hospital discharge [1]. Delayed pericardial effusion can arise within a week to 6 months post-cardiac surgery [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Loculated effusions are more common in this patient population because of pericardial adhesions or scarring associated with surgery [6,9]. Inflammation or bleeding may lead to fluid accumulation at the posterior and lateral part of the pericardium, making it difficult to visualize with Open Access *Correspondence: osman.adi@gmail.com 1 Resuscitation & Emergency Critical Care Unit, Department of Emergency and Trauma, Raja Permaisuri Bainun Hospital, Jalan Raja Ashman (Jalan Hospital), 30400 Ipoh, Perak, Malaysia Full list of author information is available at the end of the article transthoracic echocardiogram (TTE) [10,11]. Transthoracic echocardiogram has been identified as a sensitive modality to evaluate the heart for complications after cardiac surgery [12].…”
Section: Introductionmentioning
confidence: 99%